- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,756

Solve the equation $25^a+9^a+4^a=15^a+10^a+6^a$.

Last edited:

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,756

Solve the equation $25^a+9^a+4^a=15^a+10^a+6^a$.

Last edited:

- Mar 31, 2013

- 1,322

Not a complete solution butSolve the equation $25^a+9^a+4^a=15^a+10^a+6^a$.

because $(25^a > (10^a + 15^a)$ and $9^a > 6^a$ so LHS is larger

if a = 1 LHS is larger

a = 0 is a solution and there may be more non integer solutions

- Thread starter
- Admin
- #3

- Feb 14, 2012

- 3,756

Solution suggested by other:Solve the equation $25^a+9^a+4^a=15^a+10^a+6^a$.

Obviously $a=0$ is the only answer to the problem and it happens when $2^a=3^a=5^a=1$.

- Nov 4, 2013

- 428

$$(5^a)^2+(3^a)^2+(2^a)^2=5^a\cdot 3^a+5^a \cdot 2^a+3^a\cdot 2^a$$

Let $e=5^a$,$f=3^a$ and $g=2^a$. Then the given equation is:

$$e^2+f^2+g^2=ef+fg+ge$$

It is well known that $a^2+b^2+c^2 \geq ab+bc+ca$ and equality holds when $a=b=c$. Hence, in the given case: $e=f=g \Rightarrow 5^a=3^a=2^a$ and therefore, the only possible solution is $a=0$.